Outcomes of Vascularized Bone Allotransplantation with Surgically Induced Autogenous Angiogenesis in a Large Animal Model: Bone Healing, Remodeling, and Material Properties - Houben, Rudolph H.; Kotsougiani, Dimitra; Friedrich, Patricia F.; Shin, Alexander Y.; Bishop, Allen T. (Journal of Reconstructive Microsurgery, 2020)
Background Bone vascularized composite allotransplantation (VCA) is a possible alternative for the treatment of large bone defects. Clinical application of VCAs is limited by the need for life-long immunosuppression (IS). We report an alternative method to maintain bone allotransplant viability in a large animal model without the need for life-long IS by using autogenous vessel implantation.Methods Fourteen bone only VCAs were transplanted in a porcine tibia defect model with short-term IS. Two groups were used to evaluate the effect of the implantation of an autogenous arteriovenous (AV)-bundle, therefore the only difference between the groups was the patency of the AV-bundle. We radiographically evaluated bone healing and allogenic pedicle patency. AV-bundle patency and union were evaluated with micro-CT. Bone remodeling was assessed with histomorphometry and material properties were evaluated with axial compression testing and cyclic reference point indentation.Results Two subjects did not reach the final time point. Twelve tibiae healed proximally, and nine at the distal transplant–bone interface. Bone allotransplants showed their viability in the first 4 to 6 weeks by significant periosteal bridging arising from the transplant and maintained pedicle patency. Bone material properties were not affected by the implantation of an AV-bundle when compared with ligated AV-bundle controls, but diminished compared with normal bone. Significantly higher bone formation rates resulted from the implantation of a patent AV-bundle.Conclusion New periosteal bone formation and subsequent bone healing result from blood flow through the microsurgically repaired nutrient blood supply, demonstrated by maintained allogenic pedicle patency. The implantation of a patent autogenous AV-bundle has no adverse effect on material properties, but a positive effect on bone remodeling of endosteal surfaces despite thrombosis of the allogenic pedicle. Bone material properties change after transplantation compared with normal bone, although 20-weeks survival time is relatively short for the final evaluation of bone material properties.
Keywords: vascularized composite allotransplantation; bone; neoangiogenesis; reconstruction